“We Are Still Not Being Heard”: Making Black Lives Matter in Contemporary Swedish Performance - Rosenberg, Tiina (Nordic Theatre Studies, 2022)
For several years, the Black Lives Matter movement has been advocating for issues of racial justice and the representation of POC artists (people of colour) in the arts. However, it is a different kind of challenge to face up to systematic racial discrimination in Swedish society that claims itself to be both colourblind and antiracist. Contrary to the notion that if race is not mentioned, there cannot be racism, it may be argued that the performing arts in Sweden are not as open-minded and inclusive as often claimed. This article focuses on antiblackness and argues that although there are anti-racist performers and activist groups who continually address racial injustice, the response from theatre institutions has been slow. It is suggested that the performing arts in Sweden need to expand the representation of artists of colour, get better at detecting strategies of equality reluctance in theatre organisations, and improve a critical understanding of hegemonic whiteness. They also must develop a politics of iintersectionality and accountability as an approach to new ways of thinking and acting.